PENERAPAN PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION DALAM PENINGKATAN KETERAMPILAN BERHITUNG TENTANG OPERASI HITUNG PECAHAN PADA SISWA KELAS IV SDN 4 BUMIREJO - CAHYA KUSUMA, ROBBI (KALAM CENDEKIA PGSD KEBUMEN, 2015)
ABSTRACT Robbi Cahya Kusuma. APPLICATION TYPE OF COOPERATIVE LEARNING IN THE IMPROVEMENT OF TEAM ASSISTED INDIVIDUALIZATION NUMERACY SKILLS CALCULATE FRACTIONS OF OPERATIONS IN CLASS IV SDN 4 BUMIREJO. Teacher Training and Education Faculty, Sebelas Maret University of Surakarta.              The purpose of this study were (1) describe the application of cooperative learning Team Assisted Individualization can improve numeracy skills fractions in grade IV SDN 4 Bumirejo, (2) finding problems and solutions implementation of cooperative learning Team Assisted Individualization can improve numeracy skills on fractions fourth grade students of SDN 4 Bumirejo.This research is a class act. The research was conducted in three cycles. Each cycle consists of two meetings that include planning, action, observation, and reflection. The subjects were students of class IV SDN 4 Bumirejo totaling 30 students. Source of data derived from fourth grade teacher, peers as an observer, as well as fourth grade students. The technique of collecting data through observation, testing, and interviews. The validity of the data using triangulation of methods and sources. Data analysis using quantitative descriptive analysis techniques and qualitative descriptive analysis. Qualitative data analysis involves three activities, namely the flow of data reduction, data presentation and conclusion.              The results showed that (1) the application of cooperative learning Step Team Assisted Individualization can improve numeracy skills fractions, namely: a) the teacher gives LKS and media for students to learn individually along with the instructions, b) the teacher gives a quiz to students individually to get initial score, c) teachers form a heterogeneous group comprised of 4-5 students, d) student learning outcomes discussed and corrected rolling, e) the teacher explains the material presented; f) the teacher gives the evaluation to individual students, g) teachers and group rank awards to the best group, h) the teacher gives emphasis and conclusion materials .; (2) Obstacles encountered in the application of the cooperative model of Team Assisted Individualization namely: a) dependence at low academic students are more proficient students, b) the fray when discussion groups, c) students are not confident during the presentation, and, d) allocation limited time while teaching classical. Solutions to overcome these obstacles, namely a) teachers to motivate students to be independent, b) teachers guide students during the discussion, c) teachers to motivate students to want to argue, and d) the allocation of time efficiently.               The conclusions of this research is the application of cooperative learning Team Assisted Individualization can improve numeracy skills fractional Class IV student elementary school. Keywords: cooperative learning Team Assisted Individualization, mathematics, fractionsABSTRAK Robbi Cahya Kusuma. PENERAPAN PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION DALAM PENINGKATAN KETERAMPILAN BERHITUNG TENTANG OPERASI HITUNG PECAHAN PADA SISWA KELAS IV SDN 4 BUMIREJO. Skripsi, Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta.Tujuan penelitian ini adalah (1) mendeskripsikan penerapan pembelajaran kooperatif tipe Team Assisted Individualization yang dapat meningkatkan keterampilan berhitung pecahan pada siswa kelas IV SDN 4 Bumirejo, (2) menemukan kendala dan solusi penerapan pembelajaran kooperatif tipe Team Assisted Individualization yang dapat meningkatkan keterampilan berhitung pecahan pada siswa kelas IV SDN 4 Bumirejo.Penelitian ini merupakan penelitian tindakan kelas. Penelitian dilaksanakan dalam 3 siklus. Setiap siklus terdiri dari dua pertemuan yang meliputi perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Subjek penelitian adalah siswa kelas IV SDN 4 Bumirejo yang berjumlah 30 siswa. Sumber data berasal dari guru kelas IV, teman sejawat sebagai observer, serta siswa kelas IV. Teknik pengumpulan data dengan observasi, tes, dan wawancara. Validitas data dengan menggunakan triangulasi metode dan sumber. Analisis data menggunakan teknik analisis deskriptif kuantitatif dan analisis deskriptif kualitatif. Analisis data kualitatif meliputi tiga alur kegiatan yaitu reduksi data, penyajian data dan penarikan kesimpulan.Hasil penelitian menunjukkan bahwa (1) Langkah penerapan pembelajaran kooperatif tipe Team Assisted Individualization yang dapat meningkatkan keterampilan berhitung pecahan yaitu: a) guru memberikan LKS dan media kepada siswa untuk dipelajari secara individu beserta petunjuknya, b) guru memberikan kuis kepada siswa secara individu untuk mendapatkan skor awal, c) guru membentuk kelompok heterogen terdiri dari 4-5 siswa, d) hasil belajar siswa didiskusikan dan dikoreksi secara rolling, e) guru menjelaskan materi yang dipresentasikan; f) guru memberikan evaluasi kepada siswa secara individual, g) guru memberi peringkat kelompok dan penghargaan kepada kelompok terbaik, h) guru memberikan penekanan dan kesimpulan materi.;  (2) Kendala yang ditemui pada penerapan langkah model kooperatif tipe Team Assisted Individualization yaitu: a) ketergantungan siswa berakademik rendah pada siswa yang lebih pandai, b) keributan saat diskusi kelompok, c) siswa tidak percaya diri saat presentasi, serta, d) alokasi waktu saat pengajaran klasikal terbatas. Solusi untuk mengatasi kendala tersebut yaitu a) guru memotivasi siswa untuk mandiri, b) guru membimbing siswa saat diskusi, c) guru memotivasi siswa agar mau berpendapat, serta d) pengalokasian waktu secara efisien.Simpulan penelitian ini adalah penerapan pembelajaran kooperatif tipe Team Assisted Individualization yang dapat meningkatkan keterampilan berhitung pecahan siswa Kelas IV SD. Kata kunci: pembelajaran kooperatif tipe Team Assisted Individualization, pembelajaran matematika, bilangan pecahan